Cellular and biochemical science - Tripathi, G. (I.K. international Publishing House, 2010)
Intends to emphasize diversified topics of interest to postgraduate students pursuing different courses in the area of biological sciences including Zoology, Botany, Biochemistry and Biotechnology. This text is also relevant to the students of Life Sciences, Biosciences, Cell Biology, Bioengineering and Pharmacology.